THE EFFECT OF THE MIND MAPPING COOPERATIVE LEARNING MODEL TO IMPROVE THE FOURTH-GRADE ELEMENTARY STUDENTS’ LEARNING OUTCOMES IN THEME 8 AT UPT SD NEGERI 064025 MEDAN SELAYANG - Nova S.P Sitio; Patri Janson Silaban; Anna Stasya Prima Sari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the improvement of students’ learning outcomes and the process of learning implementation by applying the Mind Mapping learning model in order to find out whether there is an effect of the Mind Mapping learning model in the area where I live for students in class IV at UPT SD Negeri 064025 Medan Selayang in the academic year 2022/2023 or not. The research population is 105 students of class IV. The sample was taken by simple random sampling based on 30 students in Class IVC UPT SD Negeri 064025 in the academic year 2022/2023. The method was the experimental method. The experimental method was used to find out the effect of certain treatments on other treatments under controlled conditions. Based on the results of statistical processing, students’ learning outcomes by applying the Mind Mapping learning model are in a good category with an average score of 82.87. Meanwhile, students’ learning outcomes without applying the Mind Mapping learning model have not fulfilled the KKM that has been implemented with an average score of 47.4. By using the t-test, tcount is 8.602 while ttable is 2.042. Because tcount ≥ ttable,so Ho is rejected and Ha is accepted. It proves that there is a significant effect of the Mind Mapping learning model on the fourth-grade students’ learning outcomes at IV UPT SD Negeri 064025 Medan Selayang academic year 2022/2023.